2015
DOI: 10.14474/ptrs.2015.4.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic exercise on antioxidants in rat models with cardiomyopathy

Abstract: Objective: In this study, we aimed to test the hypothesis that aerobic exercise might exert its cardio-protective effect by preventing oxidative stress and improving cardiac function in rat models with doxorubicin-induced cardiomyopathy. Design: Randomized controlled trial. Methods: We randomly divided experimental rats into four groups: the normal group was used as a non-cardiomyopathy normal control (n=10); the control group included non-aerobic exercise after doxorubicin-induced cardiomyopathy (n=10); the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…The cardioprotective effects of exercise may improve the chemotherapy completion rate by managing dose-limiting toxicity. Many studies have consistently shown that exercise may result in the preservation of left ventricular contractile function through various mechanisms, including increased cardiac expression of antioxidant enzymes, mitochondrial function, and reduced proapoptotic signaling ( Kim and Hwang, 2015 ; Morton et al, 2019 ). The following section will summarize the potential mechanisms of exercise-induced cardioprotection against cardiotoxicity following DOX administration.…”
Section: Exercise Protects Against Dox-induced Cardiotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…The cardioprotective effects of exercise may improve the chemotherapy completion rate by managing dose-limiting toxicity. Many studies have consistently shown that exercise may result in the preservation of left ventricular contractile function through various mechanisms, including increased cardiac expression of antioxidant enzymes, mitochondrial function, and reduced proapoptotic signaling ( Kim and Hwang, 2015 ; Morton et al, 2019 ). The following section will summarize the potential mechanisms of exercise-induced cardioprotection against cardiotoxicity following DOX administration.…”
Section: Exercise Protects Against Dox-induced Cardiotoxicitymentioning
confidence: 99%
“…It has been established that exercise enhances antioxidant activities in cardiac and skeletal muscle by upregulating various cellular antioxidant systems ( Ji et al, 1998 ; Muthusamy et al, 2012 ; Wang et al, 2016 ). Kim et al reported that 2 weeks of aerobic exercise was sufficient to increase antioxidant enzyme activity, including superoxide dismutase (SOD) and catalase in the cardiac muscle of rats following DOX administration ( Kim and Hwang, 2015 ). Similarly, 2 weeks of low-intensity treadmill exercise significantly increased glutathione peroxidase (GPx), attenuating left ventricular dysfunction in rats during DOX treatments.…”
Section: Exercise Protects Against Dox-induced Cardiotoxicitymentioning
confidence: 99%
“…Kemi et al proved that 4 weeks of intensity-controlled treadmill running caused elevated ventricular weights and normalized the structure and function of the heart in female and male mice [ 89 ]. The work of Kim and Hwang discussed that a short-term (3 weeks) treadmill training was able to improve oxidative parameters in rats with cardiomyopathy [ 90 ], while the work of Cechetti et al demonstrated that a moderate-intensity treadmill training mitigated oxidative damage in the rat hippocampus, therefore contributing to cognitive improvements [ 91 ]. According to the results of Wu et al, 9 weeks of treadmill exercise has beneficial effects against depression-like behavior in rats [ 92 ].…”
Section: Aerobic Exercise Modelsmentioning
confidence: 99%